A THE EFFECT OF ALPHA THALASSEMIA, HBF and HBC ON HAEMATOLOGICAL PARAMETERS OF SICKLE CELL DISEASE PATIENTS IN IBADAN, NIGERIA. - FASOLA ATINUKE (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Sickle cell disease is a protean disease with limited data on the phenotypic and genetic variants in Nigeria. This study was conducted to provide baseline data on these variants by characterizing the existing forms of sickle cell disease and correlating these with basic hematological parameters.